A elaboração e instituição do currículo mínimo de matemática no Rio de Janeiro - Lião, Tarliz (2014)
The curriculum brings himself behind the ideas of his time, the look of his society to human affairs and other policies tacitly. Brings within its scope an entire web of historical legacies and personal branding those who dedicated their construction. And thus analyze the plots of a math curriculum is much more than looking at a content linearly arranged sequence. It is, above all, understanding that this construction was woven in order to sustain a body of ideas that say about your time. This research showed the process of elaboration and institucion of the minimum curriculum in Seeduc/RJ and brought questions and concerns of cognitive and social nature. The first reason for those concerns is the disposal of contents of the previous curriculum, which resulted in a new one. This elaboration reflected the lack of dialogue between the various social segments and professionals of the field. Governmental interests went beyond the educational objective and in this course of action democracy was subtracted from public policy actions. The perception that there wasn’t clear ideas was evident when contrasted with the elaboration of this legislation. Formatting Minimum Curriculum sought to unify all the schools in the Seeduc/RJ, within a small and not academicist utilitarian perspective, disregarding local specificities of each group. Thus, denied educational dialectic and rhetoric of academic mathematics as a school subject, that can be seen as a particular form of social relationship from which passive teachers and students who are considered minimal immerge